Use of noninvasive mechanical ventilation weaning protocol in neonatal intensive care units in Brazil: a descriptive study - Jéssica Delamuta Vitti; Antonio Adolfo Mattos de Castro; Nelson Francisco Serrão Júnior (Revista Paulista de Pediatria, 2023)
Abstract Objective: This study aimed to investigate whether neonatal intensive care units (NICUs) in Brazilian hospitals use a protocol for weaning from noninvasive ventilation (NIV), how this ventilatory support is withdrawn, and whether there is consensus among the methods used by the institutions. Methods: A cross-sectional survey was conducted from December 2020 to February 2021, based on responses to an electronic questionnaire, filled out by physical therapists working in NICU in Brazilian hospitals about the routine of physical therapy and the use of NIV and its weaning. Results: A total of 93 answers to the electronic questionnaire met the study criteria: 52.7% were from public health institutions, with an average of 15 NICU beds (15.2±15.9), 85% of the physical therapists worked exclusively in the NICU, 34.4% of the NICU had 24-h physical therapy care, 66.7% of the units use the continuous positive airway pressure (CPAP) as ventilatory mode, and 72% the nasal prong as NIV interface; 90% of the NICU physical therapists answered that their NICU had no NIV weaning protocol, with various methods of weaning reported, the most cited being pressure weaning. Conclusions: Most Brazilian NICUs have no NIV weaning protocol. The most used method among institutions, with or without a protocol, is pressure weaning. Although most of the participating physical therapists work exclusively in NICU, many hospitals do not have the recommended workload, which can be one of the negative factors in the organization of protocols and in the progress of ventilatory weaning.